Plasma Sodium in Relation with the Extracellular Fluid Volume in Chronic Hemodialysis Patients - Parlindungan Siregar (Acta Medica Indonesiana)
Aim: to obtain a causal relationship between changes in plasma sodium levels and increased extracellular fluid volume between post-hemodialysis and pre-hemodialysis on the following day or plasma sodium serves as a predictor of extracellular fluid volume. Methods: the study was conducted on 40 subjects randomly selected from the 247 chronic hemodialysis patients in Hemodialysis Unit of Nephrology and Hypertension Division, Department of Internal Medicine, Faculty of Medicine Universitas Indonesia - Cipto Mangunkusumo Hospital that met the inclusion and exclusion criteria. Their plasma sodium levels, post-hemodialysis weight and pre-hemodialysis weight on the following day were examined. Results: There was no significant difference in the plasma sodium levels between post-hemodialysis and pre-hemodialysis on the following day. However, there was a considerable differences between post-hemodialysis weight and pre-hemodialysis weight on the following day (p = 0.0000). In regression analysis that were conducted on the relationship between the difference in pre-hemodialysis sodium levels subtracted by previous post-hemodiaysis sodium levels (Y) and the difference in pre-hemodialysis weight subtractted by previous post-hemodialysis weight (X), a significant causal relationship was found with the regression formula of Y = - 2.205 + 0.937 X. Conclusion: plasma sodium levels in chronic hemodialysis patients can be used as predictors of body fluid volume or extracellular fluid volume. At each dialysis unit, the recommended weight gain for the patients are 2.5 kg-2.9 kg, in order to prevent a significant decrease in plasma sodium levels that could lead to mortality.